Fundamentals of HR analytics : a manual on becoming HR analytical - Diez, Fermin; Bussin, Mark; Lee, Venessa (Emerald Publishing Limited, 2019)
The future of the Human Resource Management profession is inextricably linked to understanding data analytics. This book provides practical, hands-on approaches to connect data to HR policies and practices to help influence overall business performance.Building on traditional HR skillsets, the book makes understanding and engaging with data analytics possible for professionals at all levels. Leveraging key statistical and financial concepts, including ROI and people productivity, and commonly available tools such as Workday and Tableau, the authors explore key skills and tasks in an accessible and illuminating way, including: data-analytic thinkingdata managementdata collectionclean-up and warehousingbuilding descriptive and predictive modelsapplying HR analytics skills and tools to workforce planning, recruitment, training, and turnover analysis.Fundamentals of HR Analytics is an essential resource for aspiring, new and experienced HR professionals across a wide range of industrial contexts, as well as data analysts working on business workforce focused projects and upper level students of HR encountering data analytics in this context for the first time.- Resumé vydavatel